2020
DOI: 10.3389/fcell.2020.620735
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into the Complexity of Craniofacial Development From a Cellular Perspective

Abstract: The head represents the most complex part of the body and a distinctive feature of the vertebrate body plan. This intricate structure is assembled during embryonic development in the four-dimensional process of morphogenesis. The head integrates components of the central and peripheral nervous system, sensory organs, muscles, joints, glands, and other specialized tissues in the framework of a complexly shaped skull. The anterior part of the head is referred to as the face, and a broad spectrum of facial shapes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 77 publications
0
30
0
1
Order By: Relevance
“…The development and differentiation of CNCCs are controlled via complex GRNs, comprising transcription factors, cis regulatory elements and epigenetic modifiers 45 . Numerous studies have identified the GRNs in premigratory and migratory CNCCs, expanding our knowledge of the mechanisms that control CNCC development at early stages 46 .…”
Section: Discussionmentioning
confidence: 99%
“…The development and differentiation of CNCCs are controlled via complex GRNs, comprising transcription factors, cis regulatory elements and epigenetic modifiers 45 . Numerous studies have identified the GRNs in premigratory and migratory CNCCs, expanding our knowledge of the mechanisms that control CNCC development at early stages 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Given that the shape of the underlying skeletal tissues is a major contributing factor to facial shape, the bone and cartilage based structures that comprise craniofacial tissues were examined (Murillo-Rincon & Kaucka, 2020). Skeletal staining showed reduced and abnormally shaped jaw cartilages, including smaller ethmoid plate, trabeculae and parachordal cartilages, reduced Meckel’s and palatoquadrate cartilages and missing basibranchial cartilages in both fos crispants and morphants ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cell migration and movements during craniofacial development facilitate interactions between different cell and tissue types, and their environment (Murillo-Rincon & Kaucka, 2020). These interactions are critical to create spatially defined sources of morphogenetic signals (e.g., WNTs, FGFs, BMP, Hedgehog), commonly referred to as signaling centers or organizers (Martinez Arias & Steventon, 2018; Murillo-Rincon & Kaucka, 2020; Perrimon, Pitsouli, & Shilo, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Multipotent neural crest cells (NCCs) direct patterning and development of the head and neck, amongst other structures, and are controlled by deeply conserved gene regulatory networks (GRNs) constituting a species-generic program ( Green et al, 2015 ; Martik and Bronner, 2021 ). The combination of these developmental and evolutionary observations, with forward genetics and human clinical models of craniofacial disease, have provided a holistic understanding of how the craniofacial prominences are patterned and skull bones develop ( Wilkie and Morriss-Kay, 2001 ; Szabo-rogers et al, 2010 ; Murillo-Rincón and Kaucka, 2020 ). However, despite this fundamental understanding of craniofacial biology across vertebrates, we still know remarkably little about how species-specific diversity arises and is patterned during development.…”
Section: Introductionmentioning
confidence: 99%
“…NCC migration into their target primordia occur in response to cues within the local extracellular environment. Here, as NCCs populate the developing prominences, reciprocal FGF, BMP, SHH, and retinoic acid signalling interactions between mesenchymal NCCs and the epithelial ectoderm and endoderm direct their spatial organization and activate GRNs responsible for proliferation, outgrowth and differentiation of the craniofacial skeleton [( Creuzet et al, 2004 ; Minoux and Rijli, 2010 ; Dash and Trainor, 2020 ; Murillo-Rincón and Kaucka, 2020 ) and references within].…”
Section: Introductionmentioning
confidence: 99%